Skin temperatures and heat transfer over wedge wings at extreme speeds of flight - Nonweiler, T. (College of Aeronautics, Cranfield, 1956)
By paying spacial attention to the wing design and altitude of flight, it is possible to ensure that the highest temperature reached at the leading edge of the wing of an aircraft, in level flight at speeds of the order of the circling velocity, need be no more than about 1000*c.